PENGARUH PERENCANAAN PAJAK, ASET PAJAK TANGGUHAN DAN ARUS KAS BEBAS TERHADAP MANAJEMEN LABA - Putri, Shafira Purnamasari; Djohar, Chaidir (LPPM Universitas Bina Bangsa, 2023)
This study aims to examine and to analyze the effect of tax planning, deferred tax asset and free cash flow on earning management in banking companies listed on the Indonesia Stock Exchange for 2017-2021 period. The population in the study was 47 banking companies. The data used in this study were secondary and the sample technique used was purposive sampling, with a sample of 11 banking companies that met the criteria with the observation for 5 years, so that the total research data is 55 samples. The source of data in this study is quantitative data originating from the annual financial reports and financial reports of banking companies. The data analysis technique uses multiple linear regression analysis with E-views version 9. The result of this study indicates that tax planning and deferred tax asset had a significant effect on earning management. While free cash flow had not a significant effect on earning management. And simultaneously, tax planning, deferred tax asset and free cash flow together had an effect on earning management